Kontradyktoryczność sytuacji zawodowej adiunktek i adiunktów w uniwersytecie = Contradictory nature of the professional situation of female and male assistant professors at the university - Bochno, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article attempts to answer the following questions: What is the professional situation of young female and male academics? What contradictions, if any, do they encounter at university? The author look sat the everyday life of female and male assistant professors working at university in a specific tangle of feudal order and neoliberal reforms.An excerpt from a small-scale survey among young university staff was used in the text. Among other things, the participants were asked about their greatest work-related worries.
Keywords: kultura uniwersytetu; sytuacja zawodowa młodych pracownic i pracowników uczelni; university culture; work situation young female and young male university staff